Effect of Work Team, School Culture on Decision Making of The Principals of The State High School in Jakarta - Oktaviany, Venny; Mukhtar, Mukhneri; Wahyudi, Mochamad (International Journal for Educational and Vocational Studies, 2019)
The objective of this study is to learn the influence of work team and school culture toward decision making of high school in Jakarta. This study was the quantitative approach, and  path analysis method was applied to analyze the data. In this study, principals of state high school have been chosen as a unit analysis and 91 samples of state high school in Jakarta. The results of this study showed that: (1) work teams have a direct positive effect on decision making; (2) school culture has a direct positive effect on decision making. At last, this study suggested that work teams and school culture were important determinants of the principals decision making.